Ekstraksi Satu Tahap Pada Makroalga Basah dan Kering Sebagai Bahan Baku Biodiesel - Vera Viena; Bahagia Bahagia; Restu Ginanjar Wibowo (Jurnal Serambi Engineering, 2019)
Macroalgae has potency to expand as one of alternatives for feedstock of biodiesel. The research has aim to extract the wet and dried macroalgae using one step method. Extraction was done by comparing the conventional methods of Bligh-Dyer, sochletation to one steps method. One step extraction method resulting a higher total lipid in wet biomass (49.67 % W.W) than dried biomass (45.67 % D.W), while conventional methods of sokhletation and Bligh-Dyer resulting total lipids of 37.67% and 39.33% Wet Weight (W.W); and 45.67% and 40.67% Dried weight (D.W), respectively. Identification of oil/lipid content of the macroalgae extract using Gas chromatography showed 3 highest peak e.i which contained 9-Octadecanoic acid (Z), methyl ester (Asam oleat) of 52.44 % area, 9-12,Octadecadienic, (Z.Z) (Asam linoleat) of 22.12 % area and  Octadecanoic acid, (CAS) methyl stearate, of 20.36 % area. Those three main fatty acid compounds were commonly found in algae oil and had great potention to be used as one of alternative feedstock for biodiesel